Indigenous knowledge in managing water resources and their role in the continuity of mountain settlements in Hawraman region - Farid Ahmadzadeh; Hassan Karimian; Mohammad Hassan Talebian; Mozhgan Khanmoradi; Majid Montazer Zohori (Dānishhā-yi būmī-i Īrān, 2022)
In this article, with the aim of investigating and evaluating the material culture left in the cultural zone of Hawraman region, the importance of water in this mountainous region and how to manage and control it has been discussed. In the field research, the results of which show these findings in this research, we tried to answer these questions, what were the principles and methods of water resources management in Hawraman region? And what role have the types of water sources and water structures played in the formation of settlements and the way of life of the communities in the region? In the results of this research, it was found that surface water sources (Sirvan River) and atmospheric precipitation, especially snow with a steep slope in the Hawraman region, have played an important role in the dynamics of the cultural landscape of Hawraman. Based on this, by creating management and transfer networks of water resources in the depths of the valleys and through digging or building canals, it creates water facilities that, while continuing and developing settlements, provide cultural, economic and social communication fields along with livelihood.he does It has been stable in Hawraman from the past until today.